Examining the Relationship Between Human Resource Practices and Job Satisfaction in a Steel Manufacturing Company - Yap, Serene Lay Siew (2011)
The purpose of this study is to examine and obtain a better perception on the influences of human resource practices on executives’ job satisfaction within the context of a steel manufacturer operating in Malaysia. A total of 120 executives across the organization participated in this study. Statistical Package for Social Science version 16 was used to analyze the data gathered through survey based questionnaires. The findings indicate a significant relationship between the dependent variable, job satisfaction and three independent variables namely result-oriented appraisals, employment security and participation. Among the independent variables, participation is considered the most important independent variable that could impact and contribute towards the job satisfaction of employees within the category of executive level. Based on the research findings, recommendations and future research opportunities were also discussed.